If it's purple, someone's gonna die : the power of color in visual storytelling - Bellantoni, Patti (Elsevier/Focal Press, 2005)
If it's Purple, Someone's Gonna Die is a must-read book for all film students, film professionals, and others interested in filmmaking. This enlightening book guides filmmakers toward making the right color selections for their films, and helps movie buffs understand why they feel the way they do while watching movies that incorporate certain colors. Guided by her twenty-five years of research on the effects of color on behavior, Bellantoni has grouped more than 60 films under the spheres of influence of six major colors, each of which triggers very specific emotional states. For example, the.